Return migration - Julia Pauli (Elgar Handbooks in Migration, 2021)
Capturing the important place and power role that culture plays in the decision-making process of migration, this Handbook looks at human movement outside of a vacuum; taking into account the impact of family relationships, access to resources, and security and insecurity at both the points of origin and destination.